1989
DOI: 10.1002/j.1460-2075.1989.tb08622.x
|View full text |Cite
|
Sign up to set email alerts
|

Supercoiled DNA is interwound in liquid crystalline solutions.

Abstract: Two structures have been proposed for supercoiled DNA: it is idealized either as a toroidal ring or as a rod of two interwound duplex chains. The latter model is the most widely depicted but the evidence remains controversial. We have worked with monomers and dimers of two plasmids, pUC8 and pKS414, of similar size and natural superhelical density. pKS414 contains a bend promoting sequence whereas pUC8 does not. In concentrated solutions these plasmids form a partially ordered liquid crystalline phase which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 37 publications
6
32
0
Order By: Relevance
“…85 Moreover, there is some evidence that the superhelical diameter is more or less constant in certain regimes. 17,82 As seen in Sec. III D, a formal analysis of the entropy is complicated, but it will be dealt with approximately, after an introduction of the case without undulations.…”
Section: Plectonemic Dna In a Nematicmentioning
confidence: 79%
See 1 more Smart Citation
“…85 Moreover, there is some evidence that the superhelical diameter is more or less constant in certain regimes. 17,82 As seen in Sec. III D, a formal analysis of the entropy is complicated, but it will be dealt with approximately, after an introduction of the case without undulations.…”
Section: Plectonemic Dna In a Nematicmentioning
confidence: 79%
“…The result is that the nematic order increases fairly weakly with the DNA volume fraction, and never becomes very high ͑␣Շ15͒. Torbet and Di Capua 82 have found that nicked circular pUC8 plasmids form a liquid-crystalline state at DNA volume fractions vӶ1. The rings definitely become more elongated, the higher the DNA concentration.…”
Section: ͑68͒mentioning
confidence: 99%
“…The theory predicts crucial role of super-helicity in DNA condensation, which has been found experimentally [19,24,28]. It was found also that the condensation conditions of closed (with σ ≃ 3 · 10 −2 ) and of open DNA are different [19].…”
Section: Discussionmentioning
confidence: 59%
“…13 In contrast to the large number of studies on liquidcrystallinity of linear DNA, 14 only a few experimental papers have addressed the arrangement of supercoiled DNA in liquid crystalline condensed states. [15][16][17] These studies do suggest that the structure of individual plectonemic supercoils changes upon condensation. However, with the scattering methods used in these papers, it is difficult to separate scattering due to intersupercoil and intrasupercoil interferences.…”
Section: 3mentioning
confidence: 82%